Subclinical TRAPS treated with canakinumab - M. Amatruda; N.S. Carucci; C. Fede; G. Conti (PAGEPress Publications, 2021)
Tumor necrosis factor receptor-associated periodic syndrome (TRAPS) is a rare autoinflammatory disease characterized by recurrent episodes of fever and systemic inflammation. We describe the case of a 19-year-old patient who was referred to our attention with frequent subclinical TRAPS episodes characterized by mild arthralgias and crampy abdominal pain, without fever. Inflammatory markers, including serum amyloid A which increases the risk of long-term amyloidosis, were persistently high also when the patient was in good general conditions. Therapy with human anti-interleukin 1β monoclonal antibody, canakinumab, led to disease control and normalization of the inflammatory markers, which are currently still normal. This clinical case supports the need to treat also subclinical TRAPS. In this respect, canakinumab is effective and reduces the risk of developing amyloidosis.